PENGARUH ASET KOPERASI TERHADAP SISA HASIL USAHA (Survey pada Koperasi Serba Usaha yang aktif di Kabupaten Serang Provinsi Banten Tahun 2016) - Sirojul Qori; Dadang Sadeli (Holistik Manajemen: Jurnal Manajemen, 2021)
This research aims to analyze the effect of the cooperative assets on the remaining results of the business (SHU) on the Multipurpose Cooperative Business that is active in Serang regency in 2016. The phenomenon that occurs in Multipurpose Cooperative in Serang Regency is in certain period of time the development of the remaining business results (SHU) that fluctuate The method used in this research is quantitative descriptive method, the sample used in this research is Multipurpose Business Cooperative active in Serang Regency as many as 66 cooperatives. The analysis tools used are classical assumption test, multiple regression, with hypothesis test using t-test and f-test. Hypothesis testing using SPSS 18.0 for windows program. The results showed that the cooperative asset has significant effect to the rest of the business result (SHU). Keywords : Cooperative Asset and Rest of Business Result